2003
DOI: 10.1097/00002030-200311210-00014
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of AIDS adult mortality by verbal autopsy in rural Malawi

Abstract: Results are consistent with those found in studies conducted in other areas of sub-Saharan Africa at earlier stages in the epidemic. They confirm that VA data can be used to estimate with a reasonable degree of confidence the distribution of AIDS- and non-AIDS-related deaths in the aggregate, even in a rural population with relatively low levels of education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…We first reviewed several pediatric and adult AIDS case validation studies. Then applied major clinical criteria of WHO’s pediatric AIDS case definition in combination with selected available common criteria used in a few adult AIDS case definitions with good validity [28,3234]. Our final AIDS case definition included any of the following conditions: 1) jaundice; 2) chronic diarrhea lasted for more than 1 month; 3) chronic fever lasted for more than 1 month; 4) wasting, defined as having at least 1 of the following symptoms – paleness, hair color change, edema legs, dry scaly skin; and 5) cough or trouble breathing lasting 3 to 27 days with fever but without a recent diagnosis of tuberculosis.…”
Section: Methodsmentioning
confidence: 99%
“…We first reviewed several pediatric and adult AIDS case validation studies. Then applied major clinical criteria of WHO’s pediatric AIDS case definition in combination with selected available common criteria used in a few adult AIDS case definitions with good validity [28,3234]. Our final AIDS case definition included any of the following conditions: 1) jaundice; 2) chronic diarrhea lasted for more than 1 month; 3) chronic fever lasted for more than 1 month; 4) wasting, defined as having at least 1 of the following symptoms – paleness, hair color change, edema legs, dry scaly skin; and 5) cough or trouble breathing lasting 3 to 27 days with fever but without a recent diagnosis of tuberculosis.…”
Section: Methodsmentioning
confidence: 99%
“…AIDS-related symptomatology was measured via response to Verbal Autopsy, a questionnaire developed to identify symptoms of AIDS in areas with over 20% HIV prevalence and where data on cause of death or illness is unavailable or unreliable 21 , 22 . Verbal Autopsy is increasingly used for determining AIDS mortality in generalized epidemics 21 , 23 , 24 and recent research found it to have 75% – 83% sensitivity and 74% – 79% specificity among adult subjects 25 . The ART use and CD4 count criteria were based on South Africa’s ART eligibility guidelines at the time of the survey 26 .…”
Section: Methodsmentioning
confidence: 99%
“…It does not permit the assignment of a precise cause of death, but instead helps to indicate the most likely cause of death given the available information [22]. In the context of AIDS, verbal autopsy has been used to estimate the distribution of AIDS and non-AIDS deaths in rural Africa with sufficient confidence but has never been used to identify causes of death among HIV patients receiving HAART [23]. Therefore, the results presented here must be interpreted with caution.…”
Section: Causes Of Deathmentioning
confidence: 96%
“…In 60 cases (64%) the likely causes of death were abstracted from hospital charts. Twenty verbal autopsies were done (18 deaths at home plus two deaths in a hospital and a remote health structure) with a median recall period of 21 months (IQR, [16][17][18][19][20][21][22][23][24][25][26][27][28]. Half needed a consensus.…”
Section: Likely Underlying Causes Of Deathmentioning
confidence: 99%